2009
DOI: 10.1111/j.1466-7657.2008.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a valid and reliable self‐efficacy in clinical performance scale

Abstract: The SECP has demonstrated evidence of content validity, construct validity, concurrent validity, internal consistency reliability and stability. Statistical analysis provided an objective tool for assessing nursing students' self-efficacy in clinical performance. It may have been fruitful to further test the instrument with students from other years of their education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 34 publications
1
51
0
6
Order By: Relevance
“…However, although the literature has addressed the clinical question of the relationship of high self-efficacy as a predictive characteristic of staff RNs and student nurses in specific clinical situations (Chang & Crowe, 2011;Cheraghi et al, 2009;Lee & Ko, 2010;Manojlovich, 2005aManojlovich, , 2005bTyler et al, 2012), with additional pressure for non-baccalaureateprepared RNs to pursue higher educational preparation, it is not clear how self-efficacy affects their success. A strong sense of self-efficacy allows for perseverance with goals despite obstacles along the way.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, although the literature has addressed the clinical question of the relationship of high self-efficacy as a predictive characteristic of staff RNs and student nurses in specific clinical situations (Chang & Crowe, 2011;Cheraghi et al, 2009;Lee & Ko, 2010;Manojlovich, 2005aManojlovich, , 2005bTyler et al, 2012), with additional pressure for non-baccalaureateprepared RNs to pursue higher educational preparation, it is not clear how self-efficacy affects their success. A strong sense of self-efficacy allows for perseverance with goals despite obstacles along the way.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The difficulties in defining competency and determining assessment criteria are still discussed in the literature. For example, some have developed assessment tools by reviewing the literature and interviewing experts, 15 carrying out focus group, 16 amending existing instrument 17 to generate indicators fitting with the goals of each institute. 12,13 Furthermore, the assessment data for competency assessment usually collected from only single source were considered too subjective, such as self-evaluation by students or rating by teachers.…”
Section: Assessing Competencymentioning
confidence: 99%
“…SE has also been found to predict clinical performance in nursing students. 18 In the field of midwifery, Jordan and Farley 19 found that SE can be enhanced in recent midwife graduates by appropriate instruction. Nevertheless, because SE is domain-specific, any assessment should focus on the specific task being assessed.…”
Section: Introductionmentioning
confidence: 98%